MPS‐IIIA mice acquire autistic behaviours with age. Issue 4 (8th March 2018) - Lau, Adeline A.; Tamang, Sarah J.; Hemsley, Kim M.
Abstract: Mucopolysaccharidosis (MPS) type IIIA is an inherited, neurodegenerative lysosomal storage disorder resulting from mutations in the SGSH gene. Consequently, N ‐sulphoglucosamine sulphohydrolase enzyme activity is reduced resulting in impaired catabolism of heparan sulphate. After an asymptomatic period, patients typically show a progressive loss of cognitive and motor skills, with death often during the second decade of life. The diagnostic criteria of autism spectrum disorders (ASD) include impaired communication and social interactions, as well as displays of repetitive behaviours and fixed interests. Children with MPS‐IIIA have been shown to exhibit decreased social communicative behaviours from approximately 3–4 years of age but behavioural stereotypies are mostly absent. In this study, we investigated whether a mouse model of MPS‐IIIA exhibited ASD‐like symptoms. The BTBR T + Itpr3 tf /J inbred mouse model of autism was used as a positive control. Male MPS‐IIIA and BTBR mice were less sociable compared with unaffected C57BL/6 male mice in the reciprocal social approach test administered at 20 weeks of age. Alternations in the frequency of social interactions was not evident at earlier stages of the disease course, suggesting an acquisition of ASD‐like social behaviours. Stereotypical behaviours were not evident in male MPS‐IIIA mice in the marble‐burying test nor was the quality of nest constructed by mice affected. Collectively, these data suggest that MPS‐IIIA mice acquire autistic social behaviours similar to the human condition, and thus they may be useful for elucidating symptom generating mechanisms and novel treatments for ASD.